Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1007/s00330-003-1861-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasound in the diagnosis, management and evolutive prognosis of acute left-sided colonic diverticulitis: a review of 208 patients

Abstract: The aim of this study was to evaluate the role of ultrasound in the diagnosis and management of acute diverticulitis and its capacity to predict posterior complications in patients undergoing medical treatment. A review was made of the histories of 208 hospitalized patients (262 admissions) initially diagnosed with acute diverticulitis over a 5-year period. Ultrasound was performed in all patients upon first admission. Diverticulitis was retrospectively classified as either simple or complicated, the latter be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 22 publications
0
31
0
8
Order By: Relevance
“…27,28 Light penetrates relatively deeply into the tissue in the NIR wavelength range of 700-900 nm. NIR fluorescence imaging has many advantages such as nonradioactivity and high …”
Section: Biodistribution In Vivomentioning
confidence: 99%
“…27,28 Light penetrates relatively deeply into the tissue in the NIR wavelength range of 700-900 nm. NIR fluorescence imaging has many advantages such as nonradioactivity and high …”
Section: Biodistribution In Vivomentioning
confidence: 99%
“…The assessment of complications such as abscesses and concealed or free perforations is possible with greater certainty on CT [56]. Studies have shown that CT is in this respect superior to US [57]. …”
Section: History-taking Basic Diagnostic Procedures Differential DImentioning
confidence: 99%
“…Complications may give the rationale for surgery. A study on consecutively hospitalized patients showed in a group with uncomplicated diverticulitis that less than 10% of the patients needed surgery whereas more than two thirds of the complicated cases had to be operated [33]. In this study the classification of complicated diverticulitis was performed by US, which indicates that image-guided conservative treatment is primarily successful.…”
Section: Conservative or Surgical Management?mentioning
confidence: 99%